Energetics of high-intensity exercise (soccer) with particular reference to fatigue - Reilly, T. (Journal of Sports Sciences, 1997)
Soccer entails intermittent exercise with bouts of short, intense activity punctuating longer periods of low-level, moderate-intensity exercise. High levels of blood lactate may sometimes be observed during a match but the active recovery periods at submaximal exercise levels allow for its removal on a continual basis. While anaerobic efforts are evident in activity with the ball and shadowing fast-moving opponents, the largest strain is placed on aerobic metabolism.On average, competitive soccer corresponds to an energy expenditure of about 75% maximal aerobic power. The energy expenditure varies with playing position, being highest among midfield players. Muscle glycogen levels can be reduced towards the end of a game, the level of reduction being reflected in a decrease in work rate. Blood glucose levels are generally well-maintained, although body temperature may rise by 2°C even in temperate conditions. The distance covered by players tends to under-reflect the energy expended. Unorthodox modes of motion - running backwards and sideways, accelerating, decelerating and changing direction - accentuate the metabolic loading. These are compounded by the extra requirements for energy associated with dribbling the ball and contesting possession. The overall energy expended is extreme when players are required to play extra-time in tournaments. Training, nutritional and tactical strategies may be used to reduce the effects of fatigue that may occur late in the game.